(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
Ecological as well as ecological and coenotical structure of flora of the «Hadyatskyi» Regional Landscape Park is specified. In relation to the leading environmental factors that are light and moisture, mesophytes (378 species; 39.9%) and heliophytes (449 species; 47.5%) are dominant in the flora of the park respectively. Geographically, mesophytes are representatives of immoral and partly boreal elements. The prevalence of heliophytes among heliomorphs indicates the prevalence of open biotopes in the park. In terms of ecological and coenotic amplitude, hemostenotopes (321 species; 33.9%) and stenotopes (299; 31.6%) occupy the dominant position. This is due to the territory being included into the ecotone section of two natural zones, resulting in many species growing at the border of their habitats and having narrow synecological amplitudes. According to species presence in typical plant groups, asectors (749; 79.1%) are absolutely dominant. Based on the coenotic specimens of the flora, the «Hadiatskyi» regional landscape park is divided into 18 ecological and coenotical groups (steppe, meadow-steppe, sandy-humid, meadow, immoral-forest, boreal-forest, forest, bog non-saline meadow-meadow, saline meadow-meadow, marsh, coastal-aquatic, aquatic, group of species with wide ecological amplitude, ruderal, vegetal and species of other groups).We point out significant participation of species in the groups belonging to zonal vegetation types for forest-steppe - immoral-forest and meadow-steppe (96 species; 10.1%). The presence of anthropogenically transformed areas within the park and adjacent territories affected floristic composition of natural groups. Ecological and coenotical analyzes of the flora show its heterogeneous character. Selected ecomorphsare quite differentiated and indicate a diverse range of ecological conditions of biotopes.